2003
DOI: 10.1007/s00431-002-1138-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydrotherapy on the incidence of common cold episodes in children: a randomised clinical trial

Abstract: This study does not demonstrate any beneficial effect of hydrotherapy on preschool children with frequent common colds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 22 publications
0
14
0
8
Order By: Relevance
“…A strong seasonality of common colds in childhood has been discussed earlier (6–8). In our study, episodes occurred predominantly during the winter months, when the incidence was threefold as high as in summer months.…”
Section: Discussionmentioning
confidence: 73%
“…A strong seasonality of common colds in childhood has been discussed earlier (6–8). In our study, episodes occurred predominantly during the winter months, when the incidence was threefold as high as in summer months.…”
Section: Discussionmentioning
confidence: 73%
“…We excluded six studies that did not meet the inclusion criteria; three were previously excluded (Baroody 2000;Grübber 2003;Yerushalmi 1980), and three were excluded from the 2017 search (Murdoch 2014;Varricchio 2013;Yu 2013).…”
Section: Excluded Studiesmentioning
confidence: 99%
“…Three studies assessed populations that were not relevant to this review (Baroody 2000;Yerushalmi 1980;Yu 2013); two investigated interventions that this review did not assess (Grübber 2003;Varricchio 2013); and one reported on an intervention and population not relevant to this review (Murdoch 2014).…”
Section: Excluded Studiesmentioning
confidence: 99%
“…Cold and warm water treatments increase blood flow and result in the training of blood vessels, which leads to a stabilization of the immune system [ 6 ]. A variety of benefits have been described, including a lowering of the frequency of coughing in respiratory tract infections and various immunological modulations [ 7 , 8 , 9 , 10 , 11 ]. As most children love water, washings, arm- and foot-baths, and walking in dew, snow, and water are perfect ways to playfully help in the prevention of common colds [ 7 ].…”
Section: Discussionmentioning
confidence: 99%